(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Intussusception is a relatively common etiology of abdominal pain in pediatric population. In adults, on the other hand, this entity is seen infrequently and a lead point can be recognized in a vast majority of cases. A 27 year old woman who was admitted in the Surgery Department of Shaheed Sohrawardy Medical College Hospital after experiencing severe upper abdominal pain associated with nausea, vomiting and fever. Later on the patient developed features of intestinal obstruction. Ultrasonography demonstrated small bowel intussusception. A jejunal intussusception 50 cm distal to the dudeno-jejunal junction was found during laparotomy. Resection and anasto mosis was performed as gut was not viable. A diagnosis of jejunal inflammatory fibroid polyp was made based on the histological findings which act as a lead point for jejunal intussusception. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 111-114